Crowdsourcing ratings for single lexical items - Elena Volodina; David Alfter; Therese Lindström Tiedemann (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave)
In this study, we investigate theoretical and practical issues connected to differentiating between core and peripheral vocabulary at different levels of linguistic proficiency using statistical approaches combined with crowdsourcing. We also investigate whether crowdsourcing second language learners’ rankings can be used for assigning levels to unseen vocabulary. The study is performed on Swedish single-word items.